2012
DOI: 10.1038/clpt.2012.202
|View full text |Cite|
|
Sign up to set email alerts
|

Prospects for Treatment of Latent HIV

Abstract: Recent advances in antiretroviral therapy (ART) have drastically improved the quality of life for people with HIV infection. However, owing to the persistence of latent HIV in the presence of therapy, patients must remain on therapy indefinitely. Currently, the solution to the HIV pandemic rests on the prevention of new infections and many decades of ART for the steadily expanding number of people infected worldwide. ART is costly, requires ongoing medical care, and can have side effects, thereby preventing it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 70 publications
0
68
0
Order By: Relevance
“…Although not completely understood, infection of activated CD4 + T cells as they are transitioning to a resting memory state may be the primary mechanism by which latency is established; direct infection of resting cells has also been demonstrated [10,21]. Several studies have suggested that HIV latency is regulated by the same mechanisms that govern host cell gene expression, including epigenetic transcriptional silencing, availability, and recruitment of host transcription factors and transcriptional interference (reviewed in [22]). There is clear evidence that cells that contain HIV DNA integrants can undergo homeostatic proliferation [23][24][25], and if these genomes are replication competent they will contribute to persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although not completely understood, infection of activated CD4 + T cells as they are transitioning to a resting memory state may be the primary mechanism by which latency is established; direct infection of resting cells has also been demonstrated [10,21]. Several studies have suggested that HIV latency is regulated by the same mechanisms that govern host cell gene expression, including epigenetic transcriptional silencing, availability, and recruitment of host transcription factors and transcriptional interference (reviewed in [22]). There is clear evidence that cells that contain HIV DNA integrants can undergo homeostatic proliferation [23][24][25], and if these genomes are replication competent they will contribute to persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HIV-1 expression can be induced in J-lat clones and primary cells from patients by HDAC inhibitors, whereas several primary cell models of latency are resistant to the effects of HDAC inhibitors. Given the complexity and diversity of latency in vivo and the varying responses of these models, information from primary cell models may be expanded by evaluating responses in more than one model 91 .…”
Section: Model Systems Of Hiv-1 Latencymentioning
confidence: 99%
“…Early attempts to reactivate virus production via global T cell activation using OKT3 and IL-2 in combination led to toxic levels of immune activation, and thus current strategies focus on reactivating the virus in the absence of T cell activation 124 . However, most of these approaches have been validated only in cell line models of HIV-1 latency, and only a few have been tested in resting CD4 + T cells that have been isolated from aviraemic patients 51,91,125128 .…”
Section: Strategies To Disrupt Latent Infectionmentioning
confidence: 99%
“…It is worth noting that similar approaches are currently being tested in cell populations latently infected with HIV-1 to promote 'reawakening' of latent HIV gene expression to allow these cells to be recognized and eliminated by HIV-specific T cells. [95][96][97] There is a very clear rational behind reducing the latent load within an individual person to limit viral reactivation; however, this clearly needs to be balanced by the risks that such an intervention may carry with it. In the case of particular clinical settings, such as immunosuppression in transplantation, we would suggest that this balance is in favour of using chemotherapeutic and/or immunological techniques to reduce the latent reservoir.…”
Section: Induction Of Immunogenic Lytic Genes In the Absence Of Immunmentioning
confidence: 99%